The Effect of Workload and Incentives on Job Satisfaction of Nurses at Djoelham Binjai Regional Hospital - Iskandar Iskandar; Yahya Tanjung (Brilliant International Journal Of Management And Tourism, 2025)
Human resources are the cornerstone of organizational sustainability, including hospitals where nurses serve as the frontline of healthcare services. The increasing demands at RSUD Djoelham Binjai, with a patient load disproportionate to the number of available nurses, present significant challenges to job satisfaction. This study aims to examine the effect of workload and incentives on the job satisfaction of non-civil servant nurses at RSUD Djoelham Binjai. The findings are expected to provide valuable insights for hospital management in enhancing nurses' performance through effective workload management and appropriate incentive schemes. Employing a quantitative research design with a survey approach, primary data were collected through questionnaires and interviews, while secondary data were obtained from relevant literature. A purposive sampling technique was applied, involving 59 non-civil servant nurses as respondents. Data analysis employed validity and reliability tests, multiple linear regression, F-tests, and t-tests, using SPSS 25. The results indicate that workload and incentives simultaneously exert a significant effect on job satisfaction, with an F-value of 27.355 and a significance level of 0.000 (<0.05). Partially, workload demonstrates a positive and significant effect on job satisfaction (t = 2.701; sig = 0.009), as do incentives (t = 2.915; sig = 0.005). These findings confirm that proportional workload distribution and adequate incentives can enhance nurses' job satisfaction. In conclusion, workload and incentives are critical factors in hospital human resource management, directly influencing the quality of healthcare services at RSUD Djoelham Binjai.